Student Disability Collectives in Australian Universities: A Desktop Review - Rebecca Ganon; Julie Kos (JANZSSA)
Student disability collectives (SDCs) are student-led groups which offer representation, social networks, and resources to university students with disability. They are run independently from the university administration. For the first time in published literature, this study has centralised and recorded information relating to the prevalence, nature, and function of SDCs. Desktop research targeting publicly available information about the prevalence, nature, and function of SDCs was undertaken to reveal a rich ecosystem of SDCs across up to 25 Australian universities. This study provides a foundational understanding of what SDCs are and what their existence can illuminate about the strength of student unionist and collectivist cultures across different institutions, for the benefit of student services practitioners and researchers. These findings have implications for future research relating to SDCs and student representation more broadly, as well as for understanding the institutional conditions from which vibrant and organic student representation emerges. Limitations relating to the currency and accuracy of publicly available online information may mediate the reliability of these findings.